Investigação do efeito neuroprotetor dos fatores de crescimento celular EPO e G-CSF em modelo de isquemia cerebral - Crico, Kamila Brison (2017)
Introduction. Stroke is a neurological syndrome due to insufficient blood supply in the central nervous system (CNS). Today it is one of the leading causes of death and disability around the world, with a majority of cases being of ischemic origin. The treatment of acute ischemic stroke is the use of the class of thrombotic agents activating fibrinolysis, which has a short therapeutic window and numerous contraindications. Recent studies point to cytokines such as the Granulocyte Colony Stimulating Factor (G-CSF) and Erythropoietin (EPO) as potential neuroprotectors in animals submitted to cerebral ischemia. However, the effects of this association are little known and were the object of this study. Methods. Male Swiss mice, young adults, divided into four groups: control group, group treated with 5000 IU/kg/ day of EPO, group treated with 100μg/kg/day of G-CSF, and group treated with both factors. All animals were submitted to occlusion of the right (temporary) and left (permanent) common carotid arteries, followed by administration of glycosidic solution (control) or drugs, 3 hours after occlusion and on the next four days, then sacrificed and the spleen and blood sample was collecteds and the brain was extracted for analysis. Results and discussion. The wet weight/body weight proportion was higher in all treated groups than control. The analysis of motor parameters by means of hanging wire, clamping force and pole test, demonstrated that surgery promoted damage in control group and these damages were prevented in the treated groups. The circulating leukocyte count was higher in the G-CSF and EPO/G-CSF groups than control, with no change in the EPO group. Already count of circulating erythrocytes was superior only in the EPO group. The macroscopic area of cerebral infarction was significantly lower in all treated groups, and there were no statistical differences between them. Treatment with EPO was not able to promote increased neuron counts, which was verified only when EPO was associated with G-CSF or with the use of G-CSF individually. Conclusion. The findings reinforce the literature data regarding the neuroprotective effects of EPO and G-CSF individually used. The association between the two growth factors did not improve the results in relation to when the drugs were used alone.